MENYELAMI KETERHUBUNGAN ANTARA FILSAFAT, ILMU DAN AGAMA - Aufani, Nabil Achmad; Sudirman (Jurnal Tawadhu, 2024)
Reason functions as a power for humans to obtain and reveal the understanding and answers that they are looking for. Philosophy, science and religion are the three main pillars that have always helped and directed humans to obtain definite answers and achieve change. Thus, researchers want to study the three in more depth and how they are related. In this research, researchers used a type of library research model. This type of research is research that prioritizes searching for the information needed based on data sources from the literature. The data analysis used in this research refers to the style of Miles and Hubberman (2014). Miles Hubberman's style has several stages, namely collecting data, reducing and analyzing data, presenting data and concluding. The relationship between philosophy, science, and religion is that philosophy offers a logical and reflective framework for contemplating fundamental questions, science provides empirical answers based on observation, while religion provides a spiritual and moral perspective. Although there is conflict between philosophy, science and religion, in practice the three interact constructively in helping humans understand the world and their place in it. This is reflected in Surah Al Isra verse 84 and Ar Rum verse 30 with a focus on the meaning of fitrah in it which means ??????? ????????? ???????.